Design, Analysis, and Experiment for Rescue Robot with Wheel-Legged Structure. (6th November 2017) - Ning, Meng; Xue, Bilun; Ma, Zefeng; Zhu, Changhong; Liu, Zihao; Zhang, Cuncai; Wang, Yao; Zhang, QiuJu
Abstract : A wheel-legged rescue robot design with strong environmental adaptability is proposed. The design presented is aimed at helping rescue workers complete their missions, such as environmental and personnel search, quickly and accurately. So it has broad application prospects. In order to achieve the advantages of simple structure, easy control, small occupation space, and wide motion range, a wheel-legged rescue robot is designed in this paper, and the robot can realize three kinds of motion states, which include wheel state, rotation center lifting process, and leg state. Then the motion states are analyzed in detail, which provides a reference for motion control. Considering the wheel state and leg state share the same structure to contact with the ground, the effect of the stiffness of wheel-legged structure to the motion performance is analyzed. Then the experiment is carried out to prove the feasibility of the structure design. This study offers a design and quantitative analysis for wheel-legged rescue robot. Furthermore, a basis for future control research and engineering applications is established.